al-Tanawub al-Lughawi Baina al-Lughah al-Arabiyah wa al-Indunisiyyah Li al-Muhadatsat al-Fashliyah Fi Madrasah Tarbiyah al-Mu’allimin al-Islamiyah Bi Ma’had al-Amin Madura - Thohir, Muhammad; Kirom, Abdul (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This reserach aims to describe the phenomenon of Arabic and Indonesian code switching at TMI al-Amien Prenduan Madura. The use of Arabic as the instruction language of classroom remains a problem because of the language backgrounds diversity both teachers and students. The problem refers to code switching between two or more languages. By using qualitative methods, the research uses recordings, observations and interviews as data collection tools. Then the data is sorted and analyzed by comparing and discussing the presentation of the data based on the theory and practice sections. The results showed that code switching between Arabic and Indonesian occurred in the classroom, either in formal or informal language variations. The causes or motives for using code switching are identified in five reasons, (1) specific theme, (2) quotation, (3) solidarity, (4) clarification, and (5) terminology. This finding rejects the view that code switching is a language defect, such as the case of language interference which occurs due to a lack of knowledge about linguistic elements. On the contrary, this finding strengthens the case of Arabic and Indonesian code switching as the deliberate use of language for certain social purposes, both teachers and students, which is supported by a variety of pragmatics and a micro-level social context, as the classroom conversation strategy.